2005
DOI: 10.1542/peds.2004-2137
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus Sepsis Associated With Probiotic Therapy

Abstract: Probiotic strains of lactobacilli are increasingly being used in clinical practice because of their many health benefits. Infections associated with probiotic strains of lactobacilli are extremely rare. We describe 2 patients who received probiotic lactobacilli and subsequently developed bacteremia and sepsis attributable to Lactobacillus species. Molecular DNA fingerprinting analysis showed that the Lactobacillus strain isolated from blood samples was indistinguishable from the probiotic strain ingested by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
275
1
16

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(299 citation statements)
references
References 35 publications
7
275
1
16
Order By: Relevance
“…46 In some rare incidents, such as patients with underlying medical conditions, the probiotic strain can become the pathogen causing an adverse event. [47][48][49] Collectively, a better understanding of the impacts of probiotics on the microbial flora is required to ascertain how best to use them to treat disease.…”
Section: Discussionmentioning
confidence: 99%
“…46 In some rare incidents, such as patients with underlying medical conditions, the probiotic strain can become the pathogen causing an adverse event. [47][48][49] Collectively, a better understanding of the impacts of probiotics on the microbial flora is required to ascertain how best to use them to treat disease.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli and Bifidobacteria are generally regarded as non-pathogenic, except a few reported cases of Lactobacillus bacteremia that seemed to occur in immunocompromised or extremely sick infants receiving high doses of Lactobacillus (Land et al, 2005). Kunz et al (2004) described L. bacteremia in two premature infants who received L. rhamnosus GG, and both of those infants had short-gut syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Dani et al [21], infants treated with Lactobacillus were shown to have an increased incidence of sepsis, and the observed decrease in NEC incidence was not statistically significant. Similarly, Land et al [22] observed cases of Lactobacillus sepsis in infants treated with probiotics. However, lactobacillemia can occur naturally and thus may or may not have been related to probiotic treatment.…”
Section: Possible Treatment For Necmentioning
confidence: 92%
“…However, point E lies in the region where the model predicts that probiotic treatment can actually be harmful, lowering the level of B L (0) needed to induce disease, for a certain range of k. For this parameter set, probiotics contribute to threshold crossing in the model, enhancing the immune response and further increasing permeability in a way that is not resolved by subsequent decreases in luminal bacterial levels. The existence of such a region may help explain clinical studies in which probiotics did not reduce the incidence of NEC and in fact led to bacterial sepsis [21,22]. Figure 6D provides a summary of predicted health and disease regions in the (k,r 1 ) plane.…”
Section: Model Predictions In the Presence Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation